Virtual Care in Undergraduate Medical Education: Perspectives beyond the pandemic. How medical education can support a change of culture towards virtual care delivery in Canada - Anawati, Michelle (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
The pandemic has led to further the importance of telemedicine, teleconsultation and technology as essential components for delivering of care in all settings. Prior to the pandemic, the instruction surrounding the safe delivery of virtual care in undergraduate medical education was sparse and informal. For care to be delivered to the high standards expected of Canadian physicians, the University of Ottawa undergraduate medical program (UGME) made the decision to define virtual care as a series of tools to facilitate and support the safe delivery of care. By focusing on virtual care as a set of tools, it provides the framework for skill development for future clinicians early in their careers and provides a critical thinking pathway to support the ever-evolving landscape of digital technology in the provision of safe, effective, timely and patient-centered care. This white paper shares our experience creating a virtual care curriculum and the possible implications for medical education.